ประสิทธิผลของการใช้แนวปฏิบัติการพยาบาลในการดูแลช่องปากสำหรับผู้ป่วยสูงอายุวิกฤตที่ใส่ท่อทางเดินหายใจ หอผู้ป่วยหนักอายุรกรรม โรงพยาบาลมหาราชนครเชียงใหม่ - นฤมล จินะคำปา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Oral care is a fundamental requirement when nursing critically ill elderly patients with endotracheal tubes. The purpose of this operational research was to evaluate the effectiveness of clinical nursing practice guidelines implementation for oral cavity care of critically ill elderly patients with endotracheal tubes, at the medical intensive care unit, Maharaj Nakorn Chiang Mai Hospital. The model of the Registered Nurses Association of Ontario (RNAO, 2009) was used as a framework for this study. The sample consisted of 40 critically ill elderly patients intubated with endotracheal tubes, and 30 registered nurses who cared for them. The study was conducted during May to August 2014. The instrument used in this study was the clinical nursing practice guidelines for care of oral cavities, developed by Supattra Nuchakul (2007). The instruments for data collection consisted of an oral assessment form, demographic data recording form for elderly patients and nurses, and satisfaction questionnaire to measure nurse satisfaction on implementation of the clinical nursing practice guidelines. Data were analyzed using descriptive statistics and the Fisher Exact Probability Test.